2021
DOI: 10.1007/s00603-021-02547-3
|View full text |Cite|
|
Sign up to set email alerts
|

Corrosion Level of Rock Bolts Exposed to Aggressive Environments in Nordic Road Tunnels

Abstract: For road tunnels in most Nordic countries, temporary rock support installed during tunnel excavation usually becomes a part of the permanent rock support. Rock bolts are the most common rock support measure in road tunnels excavated in hard rock, and their conditions over the period of tunnel operation play a significant role in the safety of these tunnels. The rock bolt types and aggressive environmental conditions considered in this research are focused on those used and observed in Norwegian and Swedish roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In fact, they strongly influence the bonding capacity of the anchoring system as well as the conduction of loads along the rock bolt length. As for the bolting material which is most often steel [72,114,115], the bolt shank is usually ribbed or smooth (Figures 6 and 7). The choice of ribbed or smooth bar depends especially on the geological conditions of host rocks.…”
Section: Bolting and Grouting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, they strongly influence the bonding capacity of the anchoring system as well as the conduction of loads along the rock bolt length. As for the bolting material which is most often steel [72,114,115], the bolt shank is usually ribbed or smooth (Figures 6 and 7). The choice of ribbed or smooth bar depends especially on the geological conditions of host rocks.…”
Section: Bolting and Grouting Materialsmentioning
confidence: 99%
“…Referring to Komurlu and Kesimal [127], the scratches caused by the installation of the bolts in the holes are also causes increasing their risk of corrosion. It is widely believed that in the event of corrosion, the strength and durability of rock bolts are greatly influenced and diminished [45,114,115,[128][129][130]. For example, as studied by Aziz et al [128], the strength of corroded rock bolts can drop sharply from 21% to 39% of their initial capacity.…”
Section: Rock Bolt Corrosionmentioning
confidence: 99%
“…From the corrosion of carbon steel structures in five road tunnels in Nordic countries, Manquehual et al [13] determined that the corrosivity levels of the tunnels fell within the range established for the extreme corrosivity level CX. Kreislova et al [14] concluded that the tunnel environment of the Mrazovka tunnel in Prague could be classified as moderate to harsh.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to corrosion, metals may dissolve in water that is low in dissolved salts and high in specific ions, such as calcium, magnesium, sodium, and potassium [28]. Several instances of damage and corrosion in tunnels have been reported due to high levels of sulfate and acidic groundwater conditions, indicating the significance of water quality in maintaining the integrity of rock supports and concrete structures in tunnels [29,30].…”
Section: Introductionmentioning
confidence: 99%